Ammianus pericarti sp. n. (Hemiptera: Heteroptera: Tingidae), the first strictly Palaearctic representative of the genus with a key to the species of the Ammianus junodi group - Lis, Barbara; Lis, Jerzy A. (Zootaxa, 2021)
Ammianus pericarti sp. n., the first strictly Palaearctic representative of the genus, is described from Agadir (Morocco) as new to the science. The species is illustrated and compared to all its morphologically similar representatives of the Ammianus junodi group; a key to this species group is also provided. Moreover, A. vanderijsti (Schouteden, 1923) is reported for the first time from the Republic of South Africa.